Growth of Api-Api (Avicennia alba) Rehabilitation in Kedaburapat Village, Rangsang Pesisir City Meranti Islands District - Khawarizmi, Dannes M.; Efriyeldi, Efriyeldi; Siregar, Yusni Ikhwan (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research was conducted in July-October 2020. Observation and data collection of Avicennia alba growth was carried out in the mangrove forest rehabilitation area, Kedaburapat, Kepulauan Meranti Regency. The purpose of this study was to analyze the growth of A. alba as on rehabilitation project based on the height and diameter planted in the coastal area of Kedaburapat, Kepulauan Meranti Regency. A survey method was conducted to obtain primary data. The data collected included the height and diameter of A. alba stems as well as measurements of water quality. The results of the research showed that the average height increase A. alba on the transect was 7.59-19.86 cm/month. The average value of the increased diameter based on the transect was 1.05-3.11 mm/month. Meanwhile, the average height by zone was 8.07-16.13 cm/month. The average value of the increased diameter by zone was 1.03-2.70 mm/month